2018
DOI: 10.1002/app.47082
|View full text |Cite
|
Sign up to set email alerts
|

Self‐healing waterborne polyurethane coating by pH‐dependent triggered‐release mechanism

Abstract: In this study, effect of high‐loaded silica capsules with corrosion inhibitor on thermal degradation and self‐healing properties of waterborne polyurethane (WPU) was investigated. Silica capsules were synthesized using an oil in water (O/W) microemulsion and WPU was prepared via the prepolymer method. Assembled capsules demonstrated pH dependent release of their core. Incorporating silica capsule as an inorganic component resulted to improve thermal and barrier properties of WPU coatings. WPU coating with 1% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Innovation in waterborne polymer protective coatings is directed toward development of functional coatings by turning their action from passive protection toward active performance. As a result, wide range of functional coatings with high performance in self‐healing, anticorrosion, or UV protection has been developed. Protection against the UV irradiation especially for outdoor applications has shown to be one of the most important tools for development of long lasting coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation in waterborne polymer protective coatings is directed toward development of functional coatings by turning their action from passive protection toward active performance. As a result, wide range of functional coatings with high performance in self‐healing, anticorrosion, or UV protection has been developed. Protection against the UV irradiation especially for outdoor applications has shown to be one of the most important tools for development of long lasting coatings.…”
Section: Introductionmentioning
confidence: 99%
“…All of the samples containing silica capsules showed better adhesion properties compare to the pure WPU coating. 21 In the study of Mirmohseni et al, 21 a sample containing 2% silica capsules showed the highest adhesion to the steel substrate. The incorporation of silica capsules more than 2% to the WPU coating decreased the adhesion properties of coating to the substrate.…”
Section: Effect Of Filler and Capsule Size On The Properties Of Thementioning
confidence: 97%
“…Smart coatings with the capability for self‐healing prolong the lifetime of metallic structures. In recent years, several strategies for self‐healing have been employed such as the release of healing agents, reversible bonds, and nanoparticles with the ability to migrate 19–23 . It has been proved that the release of the healing agent is the most well‐studied method among the other 24–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jadhav et al 25 produced microcapsules with their shells made of phenol–formaldehyde resin and their cores containing dryers, corrosion inhibitors, and linseed oil used in self‐healing, anticorrosion polyurethane coatings. Mirmohseni et al 26 studied the impact of inserting capsules filled with silica and corrosion inhibitors, on self‐healing properties and thermal corrosion of waterborne polyurethane (WPU). They made silica capsules by blending oil in water (O/W) microemulsion and the WPU through the employment of prepolymer method.…”
Section: Introductionmentioning
confidence: 99%